Comparative Study of RSA Asymmetric Algorithm and AES Algorithm for Data Security - Sholikhatin, Siti Alvi; Kuncoro, Adam Prayogo; Munawaroh, Afifah Lutfia; Setiawan, Gilang Aji (Jurusan Teknik Elektro Universitas Negeri Semarang, 2022)
There are many ways to ensure data security, one of the classic way but still effective is to use encryption. Encryption itself has two techniques or algorithms: symmetric-key (also called secret-key) and asymmetric-key encryption (also called public key). In this paper, we proposed an analysis of two algorithm of encryption: RSA and AES algorithm in term of securing digital data. The method used in this research are: RSA and AES analysis, then retrieving the result. The two algorithm is deeply and thoroughly analyzed to discover the effectiveness to secure the data. The Technological Readiness Level (TKT) is at level 6, which means demonstration of a model or prototype or the analysis result of a system or subsystem or a study in a relevant environment. The result concluded that the application of the AES encryption algorithm is more optimal than RSA encryption in digital data security. Because the encryption and decryption process of using the AES algorithm is faster, although the difference in testing time of the two encryption algorithms is not too significant. The entropy value of 4.96 in AES encryption is greater than that of RSA proving that the even distribution of characters in the chiper text code does not accumulate on certain characters so that it will be difficult to attack using frequency analysis.